1994
DOI: 10.1016/0014-5793(94)01108-7
|View full text |Cite
|
Sign up to set email alerts
|

Functional expression of nicotinic acetylcholine receptors containing rat α7 subunits in human SH‐SY5Y neuroblastoma cells

Abstract: Neuronal nicotinic acetylcholine receptors (nAChR) are made from different combinations of subunits encoded by a diverse family of genes. However, the recently cloned a7 gene codes for subunits that can form homooligomeric nAChR complexes when expressed in Xenopus oocytes.Electrophysiological studies reveal that these all-nAChR function as a-bungarotoxin (Bgt)-sensitive, quickly activating/inactivating ion channels with a unique pharmacological profile and an unusually high permeability to calcium ions. Althou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
87
0

Year Published

1995
1995
2009
2009

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 101 publications
(90 citation statements)
references
References 27 publications
3
87
0
Order By: Relevance
“…D, current-voltage curves showing peak current amplitudes ‫,ء(‬ normalized to the response in the same cell at Ϫ100 mV) as a function of holding potentials (abscissa; in millivolts) for recordings made from 6 to 12 cells and for data points as means Ϯ S.E.M. These values for channel closing are comparable to those observed the fast transient currents recorded from SH-SY5Y cells stably transfected with the rat ␣7 cDNA (7 ms; Puchacz et al, 1994a), and for ␣7-nAChR-mediated inward current responses reported in transfected ␣7-nAChR in the HEK-293 cell line (6 ms; Gopalakrishnan et al, 1995). Current findings also indicate that heterologously expressed human ␣7-nAChR-mediated peak current responses to nicotinic agonists applied at 3-min intervals and measured using K ϩ electrodes undergo "rundown", declining in amplitude with each successive application of agonist.…”
Section: Discussionsupporting
confidence: 61%
“…D, current-voltage curves showing peak current amplitudes ‫,ء(‬ normalized to the response in the same cell at Ϫ100 mV) as a function of holding potentials (abscissa; in millivolts) for recordings made from 6 to 12 cells and for data points as means Ϯ S.E.M. These values for channel closing are comparable to those observed the fast transient currents recorded from SH-SY5Y cells stably transfected with the rat ␣7 cDNA (7 ms; Puchacz et al, 1994a), and for ␣7-nAChR-mediated inward current responses reported in transfected ␣7-nAChR in the HEK-293 cell line (6 ms; Gopalakrishnan et al, 1995). Current findings also indicate that heterologously expressed human ␣7-nAChR-mediated peak current responses to nicotinic agonists applied at 3-min intervals and measured using K ϩ electrodes undergo "rundown", declining in amplitude with each successive application of agonist.…”
Section: Discussionsupporting
confidence: 61%
“…However, oocyteexpressed rat ␣7-nAChR responses are reported to be activated by the initial application of 1-100 pM A␤ (26). Other studies using acutely dissociated, rat basal forebrain neurons indicated ␤-Amyloid Inhibits Human ␣4␤2-nAChRsthat 4 M A␤ [25][26][27][28][29][30][31][32][33][34][35] or 100 nM A␤ 1-42 directly activated single channels and that 10 or 100 nM A␤ induced whole cell current responses attributable to a non-␣7-nAChR subtype (likely ␣4␤2-nAChR), also suggesting agonist-like activity of A␤ on nAChRs (43). Our observations showing (for the first time) significant functional inhibition of h␣4␤2-nAChRs by 1 nM A␤ and finding (consistent with cross-species observations) (22)(23)(24)(25)(26) inhibition of h␣7-nAChRs by 100 nM A␤ indicate that A␤ 1-42 acts as a nAChR functional antagonist with higher affinity for h␣4␤2-nAChRs than for h␣7-nAChRs.…”
Section: Discussionmentioning
confidence: 99%
“…Heterologously Expressed h␣4␤2-nAChRs in SH-EP1 Cells-Human ␣4 and ␤2 subunits (kindly provided by Dr. Ortrud Steinlein, Institute for Human Genetics, Rheinische-Wilhelms-Universitat, Bonn, Germany) were subcloned into pcDNA3.1-zeocin and pcDNA3.1-hygromycin vectors, respectively, and transfected using established techniques (32)(33)(34) into native nAChR-null SH-EP1 cells (35) to create the SH-EP1-h␣4␤2 cell line. For this and all other methods, manipulations were conducted at room temperature (23 Ϯ 1°C) unless otherwise noted.…”
Section: Methodsmentioning
confidence: 99%
“…Several such cell lines expressing functional α7 nAChRs were successfully established in recent years, including the rat α7 subunit gene expressed in SH-SY5Y human neuroblastoma cells, which also express endogenous nAChR α3, α5, α7, β2, and β4 subunit genes [33] ; the human α7 subunit gene expressed in HEK-293 cells [11] and in SH-EP1 clonal human epithelial cells [34,35] , both of which are devoid of endogenous nAChR subunits; and the rat α7 subunit gene expressed in GH 4 C 1 clonal rat pituitary cells, which endogenously express the rat nAChR β4 subunit gene [36,37] .…”
Section: Introductionmentioning
confidence: 99%